3D grain reconstruction from laboratory diffraction contrast tomography. Issue 3 (31st May 2019) - Bachmann, Florian; Bale, Hrishikesh; Gueninchault, Nicolas; Holzner, Christian; Lauridsen, Erik Mejdal
Abstract : A novel reconstruction method to retrieve grain structure from laboratory diffraction contrast tomography is presented and evaluated. Abstract : A method for reconstructing the three‐dimensional grain structure from data collected with a recently introduced laboratory‐based X‐ray diffraction contrast tomography system is presented. Diffraction contrast patterns are recorded in Laue‐focusing geometry. The diffraction geometry exposes shape information within recorded diffraction spots. In order to yield the three‐dimensional crystallographic microstructure, diffraction spots are extracted and fed into a reconstruction scheme. The scheme successively traverses and refines solution space until a reasonable reconstruction is reached. This unique reconstruction approach produces results efficiently and fast for well suited samples.